PENGARUH WAKTU PENYIANGAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG HIBRIDA (Zea mays L) VARIETAS N 37 - Lulfaizahni, Naela Mikya (PT. Anagata Sembagi Education, 2024)
This research was carried out at UPTB BP3K Sungai Lilin, Tanah Sepenggal Lintas District, Bungo Regency. This research was carried out from March 25 2014 to June 25 2014. The aim of this research was to determine the effect of weeding time and to determine the right weeding time for the growth and yield of corn plants. The design used in this research was a Randomized Group Design (RAK) with 5 treatments and 4 replications, the treatments were as follows: P0 (No weeding), P1 (weeding at 14 days after planting), P2 (weeding at 21 days after planting), P3 (weeding at 28 days after planting) and P4 (weeding at 35 days after planting). The variables observed were plant height (cm), total leaf area (cm2), age at start of flowering (DAT), net cob weight (g) and dry shelled corn yield (tons/ha). The results of the research show that different weeding times have a real influence on plant height (cm), total leaf area (cm2), age when flowering starts (DAP), net cob weight (g), but have no real effect on dry shelled corn yield ( tons/ha) in corn plants. Overall, weeding time at 14 days after planting has the best effect on the growth and yield of corn plants.